Popup republic : how to start your own successful pop-up space, shop, or restaurant - Baras, Jeremy, 1988- (John Wiley & Sons, Inc., 2016)
"PopUp Republic delves into the $50-billion dollar pop-up industry and includes stories, examples, anecdotes, case studies and a how-to guide of how to create a successful pop-up. Based on Baras' broad experience and unparalleled knowledge, PopUp Republic covers all aspects of pop-ups, including an evaluation of the U.S. vs. European/world pop-up markets; tools needed to create successful pop-ups; what constitutes a pop-up; the costs and benefits of pop-ups; what permits, insurance and licenses are needed to open a pop-up; and much more. More than just an A-to-Z guide on how to launch and operate a successful pop-up, PopUp Republic shows how pop-ups are disrupting the retail, dining and entertainment industries in this country and around the world"--